Konseling Obat Bagi Pasien Dengan Penyakit Kronis Untuk Meningkatkan Kepatuhan Terapi - Guntur Roryngosan Fara; Arlina Muhtari; Nurhaedah Nurhaedah; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Chronic diseases require continuous, long-term treatment to control symptoms, prevent complications, and improve quality of life. However, adherence to therapy in patients with chronic diseases remains low due to a lack of understanding of medications, their side effects, and the importance of regular medication use. Medication counseling is an effective strategy for improving patient adherence to therapy. This Community Service program aims to improve knowledge and adherence in patients with chronic diseases through structured medication counseling. Implementation methods include individual education and counseling, interactive discussions, and evaluation through pre- and post-tests. Results indicate increased patient knowledge regarding medication use and improved adherence to therapy after counseling. This program is expected to serve as a promotive and preventive effort in the management of chronic diseases in the community.